Profile and Trends of HIV-Infected Patients Who Use Health Department Services in Hillsborough County, Florida - Jennifer L. Logan; Lynette J. Menezes; Yiliang Zhu; Karina M. D'Souza; Hyungtae Kim; Yangxin Huang; Gloria P. Santayana (University of North Florida, 2008)
The Hillsborough County Health Department (HCHD) provides care for one-third of persons living with HIV/AIDS in Hillsborough County, Florida, who relied on public assistance for medical treatment. This study describes the demographic profile and trends for these patients. Data were obtained retrospectively from the HCHD's electronic database for 2,298 patients who enrolled for HIV/AIDS care between January 1, 2000 and December 31, 2006. The patient sample included 32.6% women, 48.7% African Americans, 19.0% Hispanics, and 30.9% Whites, with mean age 39.7 ± 9.6 years. The proportion of Hispanic enrollees increased annually (p<0.001), exceeding the Hispanic population growth rate in Hillsborough county during that same period (p=0.006). African Americans and Hispanics were more likely to have AIDS at enrollment (p<0.001). Minority women were much more likely to rely on this public-assisted HIV care compared with White female patients. Minority enrollees were also more likely to have AIDS at enrollment to the service. Nearly 98% of patients depended on government-funded health insurance. Whereas the coverage of the Ryan White increased, Medicaid and Medicare decreased for all ethnic groups (p<0.001). The rapid increase in Hispanic enrollment, the increasing dependence on the Ryan White funding, and ethnicity-gender disparities require further investigations. Monitoring demographic profiles and trends of this underserved patient cohort helps the health department assess service needs and effectively allocate existing resources to better serve this HIV-infected population.